2021
DOI: 10.3390/cryst11060703
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Drug-Loading Properties of Hydroxyapatite Particles Using Triethylamine as a Capping Agent: A Novel Approach

Abstract: Particles that modify delivery characteristics are a focus of drug-loading research. Hydroxyapatite particles (HAPs) have excellent biocompatibility, shape controllability, and high adsorption, making them a potential candidate for drug-delivery carriers. However, there are still some defects in the current methods used to prepare HAPs. In order to avoid agglomeration and improve the drug-loading properties of HAPs, the present study provides a novel triethylamine (TEA)-capped coprecipitation template method t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Previous research has shown that highly crystallized nHAs can absorb or load more drug molecules owing to their high pore volume and sufficient pore size. 4,32 ICG molecules were clearly observed in HRTEM images (Figure S3b), which strongly supported the above loading mechanism of nHA. Besides, all particles displayed a similar crystal lattice fringes, indicating that glucose modification or ICG loading after the formation of particles has no significant effect on the crystalline phases of nHA.…”
Section: Resultssupporting
confidence: 75%
“…Previous research has shown that highly crystallized nHAs can absorb or load more drug molecules owing to their high pore volume and sufficient pore size. 4,32 ICG molecules were clearly observed in HRTEM images (Figure S3b), which strongly supported the above loading mechanism of nHA. Besides, all particles displayed a similar crystal lattice fringes, indicating that glucose modification or ICG loading after the formation of particles has no significant effect on the crystalline phases of nHA.…”
Section: Resultssupporting
confidence: 75%
“…Furthermore, hydroxyapatite is naturally found in vertebrate hard tissues [3] and invertebrate shells [4]. Currently, hydroxyapatite is used for other purposes, e.g., as a heterogeneous catalyst [5], an adsorbent [6], a source of biofuel cells [7], a bioimaging agent [8], in glassy carbon electrodes [9], and in drug-delivery carriers [10].…”
Section: Introductionmentioning
confidence: 99%
“…Drug-loading research has concentrated on the creation of particle medication delivery methods over the last 10 years. Due to their biocompatibility and bioaffinity, as well as their good biological activity and great stability, bioceramic particles have garnered increased attention among these systems (Wen et al 2021 ). The majority of human bones and teeth are made of hydroxyapatite, which has the chemical formula (Ca 10 )(PO 4 ) 6 (OH) 2 .…”
Section: Introductionmentioning
confidence: 99%